Mathematical Analysis in Characterization of Carbon Nanotubes (CNTs) as possible Mosquito Repellents - Viktor Andonovic; Mimoza Kovaci Azemi; Beti Andonovic; Aleksandar Dimitrov (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
Mosquitoes are a great threat to human health to date and are a subject of interdisciplinary research involving scientists from many areas. Recently much attention has been put to novel approaches to mosquito repellent products that involve the use of novel materials, such as carbon nanomaterials, where it is essential to determine their properties. This research discusses the full molecular characterization of carbon nanotubes (CNTs) produced by electrolysis in molten salts. Each CNT has its mathematical representation due to its hexagonal lattice structure. Multi-wall carbon nanotubes (MWCNTs) are considered. The focus is on determining their structural parameters: innermost and outermost diameters, chiral indices m and n, number of walls, and unit cell parameters. Corresponding frequency parts of Raman spectra of four experimentally produced CNTs are elaborated, and Python programming and Mathematica are employed for the most accurate (m,n) assignment. Determining the chirality of these samples enables the calculation of other structural properties, which are performed now, including their graph representation. The latter enables the evaluation of different distance-based topological indices (Wiener, Balaban, Sum-Balaban, Harary index, etc.) to predict some index-related properties of the molecules.
Keywords: C61; O31; L61; 330; CNT; electrolysis; graphite; molten salts; topological indices; Python